Effect of high doses of vitamin D supplementation on dengue virus replication, Toll-like receptor expression, and cytokine profiles on dendritic cells (2023)
Dengue, caused by dengue virus (DENV) infection, is a public health problem worldwide. Although DENV pathogenesis has not yet been fully elucidated, the inflammatory response is a hallmark feature in severe DENV infection. Although vitamin D (vitD)